Critical perspectives on adolescent vocational guidance in Chile - McWhirter, Ellen Hawley; McWhirter, Benedict T (Journal of career development, 2012)
In this article, the lens of critical psychology is applied to adolescent career development and vocational guidance in Chile. The authors describe and critique the status of adolescent vocational guidance in Chile, the reproduction of extant social inequities in Chilean education, and offer recommendations for enhancing vocational guidance practice, training, and research. The authors’ recommendations may be applicable to other contexts in which social disparities limit the vocational potential of significant groups in society.